Hunting Unicorns? Experimental Evidence on Predatory Pricing - Armin Schmutzler; Aaron Edlin; Catherine Roux; Christian Thoeni (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The paper provides an experimental analysis of above-cost predatory pricing in a multi-period interaction between a monopolistic incumbent and a potential entrant. It shows that, without policy interventions, the threat of post-entry price cuts discourages entry without forcing incumbents to abstain from monopoly pricing. A policy suggested by Edlin that curtails such price cuts encourages entry and reduces the prices set by monopolistic incumbents. An alternative policy suggested by Baumol that prohibits post-exit price increases does less to encourage entry, and it does not prevent high pre-entry prices. However, as expected, it keeps post-exit prices low.
Keywords: L13; D43; C92; 330